Effects of sowing date and skipping of irrigation on growth, yield, and yield components of winter grown sunflower (Helianthus annuus L.) - Daffalla, Ahmed E.; Lazim, M.E.; Farah, S.M.; Ahmed, E.A. (Gezira Journal of Agricultural Science, 2013)
ABSTRACT The response of two winter grown sunflower cultivars (Damazin and Hysun 33) to three sowing dates (Oct 20 th , Nov 20 th   and Dec 20 th ) and  three skippings of irrigation (frequent irrigation, skipping at bud or at flowering stage) was investigated. Early sowing (Oct 20 th ) gave significantly taller plants, larger LAI, higher dry matter, greater seed yield and yield components than the second (Nov 20 th ) or third sowing date (Dec 20 th ). Oct 20 th sowing outyielded Nov 20 th and Dec 20 th sowings by about 10% and 18.2%, respectively. Plants that received skipped irrigation at bud or at flowering stages were significantly shorter, with smaller LAI and less dry matter than those of the frequent irrigation during both seasons. Also, they had significantly less seed yield by about 27.4 to 32.1% in the first season and 39.3% to  42.0 % in the second one compared with  plants that received regular irrigation.  The decrease in seed yield was attributed to a decrease in number of seeds/m 2 and 1000 - seed weight. The hybrid Hysun 33 outyielded Damazin in all parameters. The seed yield produced by hybrid was 2241 and 2042 in both seasons respectively and were 2171 and 2002 for Damazin. It is recommended that the hybrid be sown as early as October 20 with 8 irrigations for good growth and higher seed yield.